2007
DOI: 10.2486/indhealth.45.365
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Upper Limb Musculo Skeletal Disorders among Brass Metal Workers in West Bengal, India

Abstract: Brass metal work is one of the oldest cottage industries in West Bengal, India. Workers performing rigorous hand intensive jobs are likely to suffer from MSD affecting the upper limbs. The present investigation was intended to establish the prevalence of upper limb MSD among the brass metal workers and to identify the causative factors behind its development. In this study, 50 male brass metal workers (Experimental Group) and 50 male office workers (Comparison Group) were selected. For the symptom survey, a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 8 publications
10
23
0
2
Order By: Relevance
“…This result corroborated the studies of Garg [16], Gangopadhyay, Ray, Das, et al [17] and Gangopadhyay, Das, Das, et al [18]. According to Garg, severe discomfort or pain was due to heavy spinal loading and repetitive movement of body parts over an extended period [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result corroborated the studies of Garg [16], Gangopadhyay, Ray, Das, et al [17] and Gangopadhyay, Das, Das, et al [18]. According to Garg, severe discomfort or pain was due to heavy spinal loading and repetitive movement of body parts over an extended period [16].…”
Section: Discussionsupporting
confidence: 89%
“…The feeling of discomfort (pain) in different parts of the body among the workers may be due to their prolonged working hours and repetitiveness of the work; which may lead to MSD [17]. Gangopadhyay et al also showed previously that continuous bending posture, led workers to suffer from acute pain and discomfort for a long period of time, which mainly led to severe pain and MSD [18]. Sturmer, Luessenhoop, Neth, et al also concluded that repetitive strain in forced positions during long periods was a risk factor for lower back disorder [19].…”
Section: Discussionmentioning
confidence: 99%
“…The current study also indicates that the goldsmith are constantly engaged in repetitive and hand intensive jobs for several years, from which they suffer from discomfort feeling in the upper extremities of the body. Similar result was found by of Gangopadhyay et al [24], according to them highly repetitive hand intensive jobs among the brass metal workers lead to discomfort in the upper extremities. It has been also known that WMSDs are caused by multi-factorial operations of various risk factors such as poor working posture, repetitive and forceful activities and static muscle load [25,26].…”
Section: Discussionsupporting
confidence: 80%
“…A constant repetition of movements imposes a cumulative work load which can cause pain and weakness and impaired function of the muscles and other soft tissues [39]. The physiologic problems that arise from repetitive work or overuse of certain muscles, tendons and soft-tissue structures have been addressed in terms of muscle fatigue, tissue density changes, and tissue strain [40].…”
Section: Discussionmentioning
confidence: 99%